The effect of emotional, spiritual and intellectual intelligence on auditor professionalism at the inspectorate of South Sulawesi Province - Muslim Muslim; Hamzah Ahmad; Syamsuri Rahim (Universitas Hayam Wuruk Perbanas, 2019)
As government organizers—serving as the supervisory function of the civil government work unit—auditors at the inspectorate are very dependent on their professionalism. Some factors that support auditor professionalism are emotional intelligence, spiritual intelligence, and intellectual intelligence which are used as variables analyzed in this study. This study took the research object of all auditors at the Inspectorate of South Sulawesi Province, with the total of 59 people. This study uses a quantitative approach with an analytical method of linear regression. The results showed that emotional intelligence has no significant effect on auditor professionalism, while spiritual intelligence and intellectual intelligence have a significant effect on it in which it is indicated by the value of R2 that is 0.643 or 64.3%.